N-Heterocyclic carbene-catalyzed enantioselective synthesis of functionalized cyclopentenes via alpha,beta-unsaturated acyl azoliums - Mondal, Santigopal; Yetra, Santhivardhana Reddy; Patra, Atanu; Kunte, Sunita S.; Gonnade, Rajesh G.; Biju, Akkattu T. (Chemical Communications, 2014)
Highly enantioselective NHC-organocatalyzed synthesis of functionalized cyclopentenes proceeding via alpha,beta-unsaturated acyl azolium intermediates is reported. The organocascade reaction of modified enals with malonic ester derivatives having a gamma-benzoyl group involves the Michael-intramolecular aldol-beta-lactonization-decarboxylation sequence to deliver cyclopentenes in good yields and excellent ee values.